توظيف نموذج فراير في التدريس لتنمية المفاهيم النحوية لطلاب معهد تعليم اللغة العربية لغير الناطقين بها بالجامعة الإسلامية بالمدينة المنورة في مقرر التدريبات : (Employing the Frayer Model in Teaching to Develop Grammatical Concepts for Students of the Arabic Language Teaching Institute for Non-Native Speakers at the Islamic University of Madinah in the Training Course) - عادل بن منسي الفقير (At-Tajdid - Intellectual Refereed Journal, 2025)
The study aimed to explore the impact of employing Frayer’s model in teaching to develop grammatical concepts among students at the fourth level of the Arabic Language Teaching Institute for non-native speakers in in Islamic university of Madinah. The research adopted a quasi-experimental method with a single group and involved a sample of 35 students. To achieve the objectives of the study, a grammatical concepts test was utilized. The results indicated statistically significant differences at the 0.05 level between the students’ average scores on the pre-test and post-test, favoring the post-test application with an average score of 19.6. Furthermore, the study demonstrated that Frayer’s model had a significant effect on concept development, with an effect size of 0.83, which is considered high. Keywords: Fryer's Model, grammatical concepts attitude towards training course, Arabic language teaching, Islamic University of Madinah.